Understanding the regulation of APOBEC3 expression: Current evidence and much to learn. Issue 3 (15th December 2017) - Covino, Daniela Angela; Gauzzi, Maria Cristina; Fantuzzi, Laura
Abstract: The apolipoprotein B mRNA editing enzyme catalytic polypeptide‐like 3 (APOBEC3) family of cytosine deaminases plays crucial roles in innate immunity through the ability of restricting viral replication by deamination and mutation of viral genomes. The antiviral function of these proteins was first discovered when research in the field of HIV infection revealed that one member of the family, namely APOBEC3G, restricts HIV infection in T lymphocytes and that the viral infectivity factor protein drives the proteosomal degradation of this enzyme, thus overriding its antiviral function. Recent advances in cancer genomics, together with biochemical characterization of the APOBEC3 enzymes, have now implicated some family members in somatic mutagenesis during carcinogenesis. While several studies investigated the downstream consequences of APOBEC3 expression and activity, either in the context of viral infection or tumorigenesis, little is known on the upstream mechanisms regulating APOBEC3 expression. Such knowledge would be of huge importance in developing innovative approaches to strengthen antiviral innate immunity on one side and to prevent cancer development on the other. This mini review summarizes research advances on the molecular mechanisms regulating the expression of APOBEC3 family members in selected immune cell populations and cancer cells.